Fisheries impact on the Sea of Marmara ecosystem structure and functioning during the last three decades - Saygu, İsmet and Akoglu, Ekin and Gül, Güzin and Bedikoğlu, Dalida and Demirel, Nazli (Frontiers in Marine Science, 2023)
The Sea of Marmara (SoM), without doubt, is one of the most disturbed marine ecosystems of the Mediterranean basin. As a semi-enclosed and a recognized eutrophic basin, it has a unique natural characteristic by permanent stratification at 25 m depth. The SoM ecosystem is under threat by multiple stressors from excessive nutrient enrichment, overfishing, invasive species, habitat loss to the climate change. Within this study, an assessment on the SoM ecosystem structure and functioning and its changes over time have been achieved. Hence, we firstly evaluate the SoM ecosystem over a period of three decades from the 1990s to the 2010s by using three mass-balance Ecopath models, secondly, we delineate the prevailing ecosystem structure and functioning in each period, thirdly we determine how the fishing impact contributed to the changes in the SoM since the 1990s and finally establish a baseline for the management and future studies of the ecosystem. The comparison of the models’ results for three consecutive time periods of the SoM showed that the energetic capacity of the ecosystem decreased significantly over the three decades while the decrease in cycling indices indicated that the SoM ecosystem became fragile to anthropogenic disturbances. According to ecosystem theory indices, the SoM is an immature ecosystem at a stage of autotrophic succession, with a very high total primary production, much more above unity that greatly exceeds total respiration. Our results highlighted that the SoM ecosystem was under bottom-up control exerted by mesozooplankton; however, anchovy was a bottleneck in energy transfers to higher trophic levels creating also a wasp-waist control in the food-web. The bycatch of demersal species with long life span, sharks and rays, brought them to the brink of going commercial extinction. Overall, the changes in the SoM ecosystem were due to the trophic cascades exerted by fisheries exploitation in addition to the changes in the productivity of the system. We conclude that the concomitant impacts of stressors on the SoM have been so diverse that an immediate action plan is required. Therefore, we propose a tentative outlook that will help in ecosystem monitoring and better management of the SoM.